Development of the educational comic book as a media to prevent bullying behavior among students at SMPN 2 bua - Fakhriani Azzuhrah Fakhrudin; Abdullah Pandang; Suciani Latif (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to (i) describe the needs for an educational comic book as a media to prevent bullying behavior in SMPN 2 Bua; (ii) discover the prototype of an educational comic book as a media to prevent bullying behavior in SMPN 2 Bua; (iii) determine the validity of an educational comic book as a media to prevent bullying behavior in SMPN 2 Bua; and (iv) determine the practicality of an educational comic book as a media to prevent bullying behavior in SMPN 2 Bua. This study used interviews and questionnaires for data collection. Both qualitative and quantitative approaches were used for data analysis. For the validity, the first expert gave a score of 82.5%, while the second expert gave a score of 88%, indicating that the product was in the good category. Therefore, the product was determined to be valid, useful, feasible, accurate, and practical to use. The results of the small group testing through questionnaires, the results of the students’ response questionnaire obtained an average score of 89.16%, while the results of the school counselor's response questionnaire obtained an average score of 92.5%, which was categorized as good. Therefore, based on these results, it can be concluded that the educational comic media was acceptable and feasible to be used by students and the school counselor.